Automatic Signal Quality Index Determination of Radar-Recorded Heart Sound Signals Using Ensemble Classification - Shi, Kilin; Schellenberger, Sven; Michler, Fabian; Steigleder, Tobias; Malessa, Anke; Lurz, Fabian; Ostgathe, Christoph; Weigel, Robert; Kölpin, Alexander (IEEE Transactions on Biomedical Engineering, 2019)
Objective: Radar technology promises to be a touchless and thereby burden-free method for continuous heart sound monitoring which can be used to detect cardiovascular diseases. However, the first and most crucial step is to differentiate between high- and low-quality segments in a recording to assess their suitability for a subsequent automated analysis. This paper gives a comprehensive study on this task and firstly addresses the specific characteristics of radar-recorded heart sound signals. Methods: To gather heart sound signals recorded from radar, a bistatic radar system was built and installed at the university hospital. Under medical supervision, heart sound data were recorded from 30 healthy test subjects. The signals were segmented and labeled as high- or low-quality by a medical expert. Different state-of-the-art pattern classification algorithms were evaluated for the task of automated signal quality determination and the most promising one was optimized and evaluated using leave-one-subject-out cross-validation. Results: The proposed classifier is able to achieve an accuracy of up to 96.36% and demonstrates a superior classification performance compared to the stateof- the-art classifier with a maximum accuracy of 76.00 %. Conclusion: This paper introduces an ensemble classifier that is able to perform automated signal quality determination of radar-recorded heart sound signals with a high accuracy. Significance: Besides achieving a higher performance compared to state-of-the-art classifiers, the presented study is the first one to deal with the quality determination of heart sounds that are recorded by radar systems. The proposed method enables contactless and continuous heart sound monitoring for the detection of cardiovascular diseases.<br
Keywords: biomedical engineering; biomedical informatics; biomedical signal processing; heart sounds; medical radar; pattern recognition; phonocardiography